Foreign Investment and the Terms of Trade - Whittlesey, Charles R. (Quarterly Journal of Economics, 1932)
Exchange and ultimate effects of foreign investment, 444. — Changes in productivity under simple conditions, 445. — Relation to ratios of productive efficiency, 447. — Changes in productivity under complex conditions, 448. — Distribution of gain from foreign investment, 454. — Significance of diversification, 458. — Linked competition, 461. — Summary of conclusions, 463.